2018
DOI: 10.1186/s12544-018-0297-5
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability assessment of retail logistics solutions using external costs analysis: a case-study for the city of Antwerp

Abstract: Purpose: Policy implementation in the logistics sector might drive unexpected side-effects which sometimes undermine the performance of key economic activities of logistics operators, especially in areas such as transport service, sustainability of operations, etc. Especially for the latter, there is a lack of understanding how the sustainability performance if retail logistics solutions is impacted on by policy implementation and, in turn, by operators' responsive measures. This paper conducts a sustainabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Khan et al [56] modeled the impact of G&SL performance on the countries' economic development and macro-level social and environmental indicators. Papoutsis et al [57] and Solomon et al [58] both maintained that logistics sustainability is closely related to operational efficiency and social acceptance from an economic and environmental perspective. Through the expert scoring, Morana and Gonzalez-Feliu [59] identified the most prominent factors affecting the sustainability of urban logistics are monetary saving, services quality, and customers' satisfaction rate (economic), pollution emissions and congestions (environmental), and the number of employment created/destroyed (social).…”
Section: Evaluation On the Social Environmental And Economic Impactsmentioning
confidence: 99%
“…Khan et al [56] modeled the impact of G&SL performance on the countries' economic development and macro-level social and environmental indicators. Papoutsis et al [57] and Solomon et al [58] both maintained that logistics sustainability is closely related to operational efficiency and social acceptance from an economic and environmental perspective. Through the expert scoring, Morana and Gonzalez-Feliu [59] identified the most prominent factors affecting the sustainability of urban logistics are monetary saving, services quality, and customers' satisfaction rate (economic), pollution emissions and congestions (environmental), and the number of employment created/destroyed (social).…”
Section: Evaluation On the Social Environmental And Economic Impactsmentioning
confidence: 99%
“…This proposed method could be applicable to other manufacturing systems to implement production-logistics collaboration. In this way, Papoutsis et al [23] conducted a sustainability analysis of concrete innovative and already tested retail logistics solutions addressing the research question "what are the effects of retail logistics solutions on total costs and sustainability performance?" For the analysis, they developed and applied an indicator-based framework based on the key sustainability components (economy, environment, society) and enriched by the addition of the transport component.…”
Section: Techniques For Optimization In Logisticsmentioning
confidence: 99%
“…According to the literary review carried out, it was found that there are different investigations in relation to logistic processes, although some authors have used simulation models in their investigations. These do not focus on the systematic optimization of logistics costs, so: Ugarte [4] focused on evaluating environmental impacts in logistics processes; Guo et al [22] explored if there is an adequate allocation of resources between production and logistics systems; Papoutsis [23] investigated the key factors affecting retail logistics solutions in total costs and sustainability performance; Tamás [26] conducted research to improve the programming of batches that will occur in intermittent production systems.…”
mentioning
confidence: 99%
“…Papoutsis et al [5] compare scenarios of retail business on data of one retail company in Antwerp. The results of the analysis bear witness of the complexity of retail logistics within an urban planning context and of the fact that sustainability of logistics, in terms of economic and environmental concerns, goes hand in hand with operational effectiveness and social uptake.…”
Section: Topical Collection On the Role Of Planning Towards Sustainabmentioning
confidence: 99%